Case study of the efficient use of cognitive diversity as a drive to improve efficiency and increase innovation in the Company - Okpu Yo, Agbor Takang; Ryška, Tomáš, 1976-; Sieber, Patrik, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
Diversity and inclusion is a topic gaining significance as it relates to the differences in the workforce and the globe at large. The aim of this thesis to evaluate the impact of diversity and inclusion has on efficiency and innovation. This research follows relevant literature review on the topic of efficiency and inclusion and their applicabilty in the workplace. The research strategy is a qualitative ethnographic study, conducted in the form of a case study in the organization of Edwards Lifesciences AG, located in Prague. The research questionnaire focuses on understanding the ways the management improved the diversity and inclusion from the year 2017 to 2022. Additionally, a participative observation was conducted together with 12 qualitative interviews with gatekeepers and managers within the organization. The data collected was qualitative in nature, it is a reflection of the influence of diversity and inclusion on the efficiency of business processes and innovations. Furthermore, a concise evaluation of the impression of diversity and inclusion for the organization and the grading on the footprint of diversity and inclusion were documented in the organization in the Czech Republic.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses